Making Sense of Immigrant Work Integration An Organizing Framework - Nardon, Luciara (International Marketing and Management Research, 2022)
This open access book explores the wicked problem of immigrant work integration, with specific examples from Canada. Bringing together a variety of disciplinary perspectives, it discusses immigrant work integration as a process of sensemaking, involving multiple actors (immigrants, organizations, communities, and governments) and multiple scales (individual, interactional, organizational, and institutional). The authors identify key players, issues, practices of support, and avenues for future research. This work contributes to enhancing the social impact of academic research by providing a comprehensive overview of the field of immigrant work integration for researchers in global mobility and organizational studies, as well as practitioners.